Land use and occupation and pesticide contamination assessment in honey from Africanized honey bees (Hymenoptera: Apidae) using gas chromatography-mass spectrometry - FERNANDO DA CUNHA; EMERSON D. CHAMBÓ; SILVIA RENATA M. COELHO; SIMONE CRISTINA CAMARGO; DRÁUZIO C. GAMA; REGINA C. GARCIA (Anais da Academia Brasileira de Ciências)
Abstract We examined pesticide contamination in honey from Africanized honey bees in two different seasons, and evaluated the concentration and incidence of these compounds in georeferenced apiaries to provide relevant information for food safety and environmental quality. The land use and occupation of the region were evaluated by selecting 15 apiaries and georeferencing three randomly selected colonies of Africanized honey bees within each apiary. Honey samples were collected during two seasons, and three organochlorine pesticides (p.p`-DDE, Mitotane and Bicyclo[2.2.1]) and four organophosphate pesticides (Ethoprophos, Methyl Parathion, Chlorpyrifos and Fenchlorphos) were analyzed in the honey using gas chromatography-mass spectrometry. 80% of the apiaries showed a predominance of agricultural land use in the foraging areas of the bees. There was a higher concentration of pesticides in samples collected during Season I compared to Season II. There were differences in the proportion of samples contaminated with pesticides between seasons. Some honey samples showed concentrations of the chlorpyrifos pesticide above the levels recommended by Brazilian legislation. Pesticide contamination of honey is not limited to specific application season, indicating the persistent presence and easy availability of pesticides, including banned pesticides not sold or prescribed by agronomists, potentially smuggled from neighboring countries.